Financial literacy and personal savings: a case of teachers in selected church-aided primary schools in mukono municipality - Barbra Nuwakunda (Uganda Christian University, 2026)
The study examined the effect of financial literacy on personal savings of teachers in selected Church-aided primary schools in Mukono Municipality. It specifically focused on; analyzing the budgeting skills on personal savings of teachers, investigating the investment knowledge teachers have on personal savings of teachers, assessing the personal savings behaviors of teachers in Church-aided primary schools, and examining the relationship between financial literacy and personal savings among teachers in Church-aided primary schools in Mukono Municipality. The study was carried out using a cross sectional survey research design where quantitative research approach was also used. The data was collected using questionnaires and during data collection, stratified sampling method was used. A sample size of 66 respondents who are selected teachers from both Bishop‟s East and West Primary Schools was also used in the study. The study findings showed that monetary literacy significantly affected private saving among instructors within Church-aided principal faculties in Mukono Municipality, with strong proof of powerful budgeting practices, investment know-how, disciplined saving behaviors, and excessive ranges of monetary cognizance. instructors who showed skills and abilities in earnings administration, budgeting, investment choice-making, and monetary planning have been much more likely to store regularly, make plans for the future, and preserve monetary balance, a fact that became further confirmed through a strong positive correlation among monetary literacy and private saving (r = 0.622, p < 0.01) and regression results that confirmed that instructors' skills and abilities in budgeting (β = 0.396, t = 5.426, p = 0.000) and investment know-how (β = 0.243, t = 3.668, p = 0.000) significantly predicted private saving. Lastly, the study proposed the importance of reinforcing teachers‟ monetary literacy thru effective finances preparation, progressed funding concept, strict saving discipline, and improvement of competencies in profits control, monetary planning, and analysis of monetary statistics, among centered monetary literacy schooling thru academic establishments and stakeholders for effective and knowledgeable monetary choice-making, saving, and stability.
Undergraduate